The In Vitro Efficacy of Activated Charcoal in Fecal Ceftriaxone Adsorption among Patients Who Received Intravenous Ceftriaxone - Pattama Torvorapanit; Kornthara Kawang; Pajaree Chariyavilaskul; Stephen J Kerr; Tanittha Chatsuwan; Voraphoj Nilaratanakul (Antibiotics, 2023)
Broad-spectrum antibiotics can kill both pathogens and gut microbiota. Reducing exposure to excess intestinal antibiotics could theoretically protect gut microbiota homeostasis. Recently, engineered charcoals, gel microparticles, and resin beads have demonstrated efficacy in intestinal antibiotic adsorption in animal studies. We report the first in vitro study evaluating human fecal antibiotic adsorption efficacy of conventional activated charcoal (AC). We collected fecal samples from eight patients who received intravenous (IV) ceftriaxone after admission to King Chulalongkorn Memorial Hospital, Thailand, during January–March 2020. Fecal ceftriaxone was measured by indirect competitive enzyme-linked immunoassays. Three different doses of AC were mixed with fecal samples under a specified protocol. The geometric mean reduction in fecal ceftriaxone concentration when mixed with AC 30 mg/g feces was 0.53 (95% CI 0.33–0.85, p-value < 0.001), meaning 47% adsorption efficacy. Increased adsorption was found with higher doses, 71% and 87% for AC 150 and 500 mg/g feces, respectively. In conclusion, the usual food-poisoning-care dose of conventional AC, 30 mg/g feces, demonstrated dose-dependent and significant fecal ceftriaxone adsorption. Conventional oral AC might be a pragmatic and inexpensive option for the protection of gut microbiota in patients receiving IV ceftriaxone. However, in vivo studies and microbiome analysis are needed for further evidence.